Measurement of the W+W-γ cross section and direct limits on anomalous quartic gauge boson couplings at LEP - Dova, María Teresa (2000)
The process eqeyaWqWyg is analysed using the data collected with the L3 detector at LEP at a centre-of-mass energy of 188.6 GeV, corresponding to an integrated luminosity of 176.8 pby1 . Based on a sample of 42 selected WqWy candidates containing an isolated hard photon, the WqWyg cross section, defined within phase-space cuts, is measured to q y be: s WW s290"80"16 fb, consistent with the Standard Model expectation. Including the process e e anngg, limits g are derived on anomalous contributions to the Standard Model quartic vertices WqWygg and WqWyZg at 95% CL: y0.043 GeVy2-a rL2-0.043 GeVy2 , y0.08 GeVy2-a rL2-0.13 GeVy2 , y0.41 GeVy2-a rL2-0.37 GeVy2